Materialism, Subjective Happiness and Epistemic Beliefs of Students of Economics in Hamburg, Graz and Bangkok: A Cross Cultural Study and Discussion Regarding Economics Education - Benton, Matthew Hale [Verfasser]; Casper, Marc [Verfasser]; Karner, Stefanie [Verfasser]; Tafner, Georg [Verfasser] (My University, 2018)
"Personal attitudes towards owning, well-being and knowing seem central to understanding economic ideologies and the way people engage in educational propositions. For example: Is there a bias in choosing study paths according to personal attitudes on materialism? Do students of economics and business tend to be more materialistic (and probably less happy) than other students? Also, especially concerning educational studies: Do students' epistemic beliefs correlate noticeably with their choice of study programs? For a better understanding of students and the development of quality economics education, we partake in an international survey (Sabri et al. 2016) combining established scales of materialism (Richins 2004; Richins/Dawson 1992; Müller et al. 2013), happiness (Lyubomirsky/Lepper 1999) and epistemic beliefs (Paechter et al. 2013; Schraw et al. 2002). This paper compares results from different study groups of the involved universities, discussing general trends and cultural differences with special regard to current problems of economics education and implications for its future course." (authors' abstract; BIBB-Doku)

"Persönliche Einstellungen und Überzeugungen zu Besitz, Wohlbefinden und Wissenserwerb scheinen zentral, wenn es um das Verständnis ökonomischer Ideologien und die Wahrnehmung von Bildungsangeboten geht. Zum Beispiel: Wie wirken sich die persönlichen Überzeugungen zu Materialismus auf die Wahl eines Studiengangs aus? Neigen Studierende wirtschaftswissenschaftlicher Studiengänge dazu, materialistischer (und möglicherweise unglücklicher) zu sein als andere Studierende? Und insbesondere mit Blick auf pädagogische Studiengänge: Gibt es Zusammenhänge zwischen den epistemischen Überzeugungen der Studierenden und der Studienwahl? Zum besseren Verständnis der Studierenden und zur Entwicklung qualitativer ökonomischer Hochschullehre beteiligen wir uns an einer internationalen Erhebung (Sabri et al. 2016), in der etablierte Skalen zu Materialismus (Richins 2004; Richins/Dawson 1992; Müller et al. 2013), Glück (Lyubomirsky/Lepper 1999) und epistemischen Überzeugungen (Paechter et al. 2013; Schraw et al. 2002) kombiniert werden. Dieser Beitrag vergleicht die Ergebnisse aus verschiedenen Studierendengruppen der beteiligten Universitäten. Wir diskutieren gemeinsame Trends und kulturelle Unterschiede vor dem Hintergrund aktueller Herausforderungen Ökonomischer Bildung, sowie Implikationen für deren künftige Ausrichtung." (Autorenreferat; BIBB-Doku)
Keywords: S 1.4 Hochschulbildung; G 2.4.2 Lebenskonzepte, -stile, Werte; Ökonomische Bildung; Studium; Studienfachwahl; Einstellung; Materialismus; Glück; Epistemologische Überzeugungen